PENGARUH KEGIATAN PENGAJIAN REMAJA MAJELIS TAKLIM “NURUL ILMI” DAN KONTRIBUSINYA TERHADAP PEMBENTUKAN AKHLAK GENERASI MUDA (Studi Kasus di Desa Kersana Kec. Kersana Kab. Brees) - Mansyur Hidayat Pasaribu; Muhammad Rizki Syahputra (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
This study aims to determine the Model of Superior Madrasah Development and Supporting Elements of Superior Madrasah Development. This study uses a library research method by collecting a number of books, magazines, journals, lifets relating to the problem and research objectives. Collecting data with the results of previous studies that support data on the research theme designing a madrasa education management development model with the research process starting with the stages of identifying, finding relevant information, analyzing the findings, and then developing and expressing them into new findings related to the education management development model. at the madrasa. The key to building a superior madrasah must meet several criteria, namely the availability of professional education personnel, complete facilities and infrastructure, a modern, transparent and democratic professional management system, and a curriculum that is in accordance with the needs of society and the challenges of the modern world. In addition, madrasas also need to pay attention to continuously improve quality, develop innovation and creativity, and build a network of cooperation (networking), so that inputs and outputs are good. In other words, developing superior madrasas requires effective and functional carrying capacity, such as superior human resources, infrastructure (representative study rooms, libraries and laboratories), supporting facilities (boarding/ma'had, mosque or prayer room). Excellent madrasah must be designed according to the vision-mission and institutional objectives, analyze the needs of the academic and institutional system, and understand the geographical and cultural context. Meanwhile, its development requires togetherness and a collective mindset, continuous innovation, and utilizing information technology, building open and principled leadership, improving the quality of madrasa governance, improving the quality of the new student recruitment system, increasing the quantity and quality of extracurricular activities, and improving the quality of the extracurricular activities. teaching and professional development activities.